2003
DOI: 10.1038/sj.bjc.6600887
|View full text |Cite
|
Sign up to set email alerts
|

Phase I–II study of docetaxel and ifosfamide combination in patients with anthracycline pretreated advanced breast cancer

Abstract: Given the established individual activity of docetaxel and ifosfamide in anthracycline pretreated advanced breast cancer, the present phase I -II study aimed to define the maximum tolerated dose (MTD), the dose-limiting toxicities (DLTs), and activity of the docetaxel -ifosfamide combination in this setting. Cohorts of three to six patients with histologically confirmed metastatic breast cancer after prior anthracycline-based chemotherapy were treated at successive dose levels (DLs) with escalated doses of doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…However, these data should be deemed rather premature and the schedule and doses administered were largely suboptimal; docetaxel 50 mg/m 2 on day 1 and ifosfamide 1.2 g/m 2 /day× 3days [31], compared to those defined in the study of Pronk et al [12], as well as in our phase I-II study [13]. In the aforementioned phase I-II study of Pagani et al [28], evaluating the paclitaxel/cyclophosphamide doublet, a dose-response effect was suggested for pretreated patients, with a lower RR reported for those receiving <1,500 mg/m 2 of cyclophosphamide [28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, these data should be deemed rather premature and the schedule and doses administered were largely suboptimal; docetaxel 50 mg/m 2 on day 1 and ifosfamide 1.2 g/m 2 /day× 3days [31], compared to those defined in the study of Pronk et al [12], as well as in our phase I-II study [13]. In the aforementioned phase I-II study of Pagani et al [28], evaluating the paclitaxel/cyclophosphamide doublet, a dose-response effect was suggested for pretreated patients, with a lower RR reported for those receiving <1,500 mg/m 2 of cyclophosphamide [28].…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by the Ethical and Scientific Committees of the participating institutions and informed consent was obtained from each patient before study entry. A number of patients included in the present study (41 out of 71) has been reported previously as a part of a phase I/II study of the docetaxel+ifosfamide combination that defined the MTD and demonstrated a preliminary activity of the regimen [13].…”
Section: Patient Selectionmentioning
confidence: 98%
See 2 more Smart Citations
“…phase I/II studies that have combined ifosfamide with other agents for treating advanced breast cancer patients, such as doxorubicin, (13) paclitaxel (14) and docetaxel (15,16) and these studies have demonstrated the feasibility of considerably high ifosfamide doses as well as the substantial activity of the employed combinations.…”
Section: Purposementioning
confidence: 99%